2021
DOI: 10.3233/jad-200890
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneity of Amyloid Binding in Cognitively Impaired Patients Consecutively Recruited from a Memory Clinic: Evaluating the Utility of Quantitative 18F-Flutemetamol PET-CT in Discrimination of Mild Cognitive Impairment from Alzheimer’s Disease and Other Dementias

Abstract: Background: With the more widespread use of 18F-radioligand-based amyloid-β (Aβ) PET-CT imaging, we evaluated Aβ binding and the utility of neocortical 18F-Flutemetamol standardized uptake value ratio (SUVR) as a biomarker. Objective: 18F-Flutemetamol SUVR was used to differentiate 1) mild cognitive impairment (MCI) from Alzheimer’s disease (AD), and 2) MCI from other non-AD dementias (OD). Methods: 109 patients consecutively recruited from a University memory clinic underwent clinical evaluation, neuropsychol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 71 publications
(109 reference statements)
0
6
0
Order By: Relevance
“…Considering that the sample size was not large enough might be the possible reason why the results were different than expected; especially, the sample size of the NC group was small due to the difficulty in recruiting normal subjects. A previous study using 18 F-flutemetamol PET showed that the differences of both the left and right occipital SUVR between subjects with MCI and AD were statistically significant with high efficacy ( bao et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Considering that the sample size was not large enough might be the possible reason why the results were different than expected; especially, the sample size of the NC group was small due to the difficulty in recruiting normal subjects. A previous study using 18 F-flutemetamol PET showed that the differences of both the left and right occipital SUVR between subjects with MCI and AD were statistically significant with high efficacy ( bao et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Participants with other neurological conditions (such as stroke, tumors, infection, movement disorders, demyelinating diseases, seizure, and migraine) and psychiatric disorders were excluded. Detailed descriptions of inclusion and exclusion criteria for the participants have been reported previously [ 27 , 28 , 29 ]. AD and MCI were defined mainly according to the core criteria of AD and MCI from the National Institute on Aging-Alzheimer’s Association separately [ 4 , 17 ].…”
Section: Methodsmentioning
confidence: 99%
“…Filtered back-projection reconstruction was adopted with a slice thickness of 2 to 4 mm, and matrix size was 128 × 128 with a pixel size of 2 mm. Details of the acquisition scheme have been reported previously [ 27 ].…”
Section: Methodsmentioning
confidence: 99%
“…The diagnosis of cognitive impairment was determined by the consensus between a neuroradiologist (HKFM) and two geriatricians (YFS, PC, or JSKK) based on the findings from clinical (baseline and follow-up) and neuropsychological (HK-MoCA) evaluations, 18 F-flutemetamol PET-CT scans, structural MRI, MRA, and ASL [ 20 ]. The diagnoses of MCI were determined using the clinical criteria from [ 23 ] and those of AD from [ 24 ] together with a positive Aβ diagnosis.…”
Section: Methodsmentioning
confidence: 99%
“…The central hypothesis of this study is that SC-FC coupling is a novel biomarker for the characterization of the effect of Aβ accumulation along the AD continuum. We have previously shown that the majority of MCI patients can be distinguished from AD patients based on 18 F-flutemetamol PET-CT scans with high efficacy [ 20 ]. Those who could not be differentiated were the MCI_Aβ+ patients who had similar Aβ retention as AD patients.…”
Section: Introductionmentioning
confidence: 99%